Dynamism of Instructional Aids on Teaching Physical Education Among Secondary School in Kogi State, Nigeria - Ajadi Memunat Tunrayo; Falaye Elijah Kayode; Adebayo Babatunde Samson (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
This study examined Dynamism of instructional aids on teaching of Physical Education among secondary school in Kogi State, Nigeria. Descriptive research design of survey type was used. The population for this study consist all Secondary School students within the study area. Purposive and random sampling techniques were used to select 394 respondents. Researcher–structured questionnaire was used for data collection. The instrument was validated by three lectures in the department of Human Kinetics Education, University of Ilorin and tested for reliability. A correlation coefficient of 0.85 was obtained. The administration of the instrument was done by the researchers. The data collected were analysed using Pearson Product Moment Correlation (PPMC) and percentage count. The results revealed that, there was a significant relationship between behavioural benefits and cognitive benefits of instructional aids on teaching of Physical Education among Secondary Schools. The study concluded that uses of instructional aids are significant to quality teaching of physical education in schools. The study recommends that effective uses of instructional aids plays a significant role in teaching and learning of Physical Education in schools which also enhance the behavioural and cognitive benefits of the students.